Marthandavarmma - C V Ramanpillai (DC Books, 1992)
Marthanda Varma (1891) is the first of a trilogy of historical novels which C.V. wrote on the royal family of the erstwhile state of Travancore. The other two are Dharmaraja (1913) and Ramaraja Bahadur in two parts (1918-1920). Marthanda Varma on the surface, is a historical romance, but its subtext is a political one of contemporary significance. In the novel there is a subplot with Subhadra at the centre. Through what she does or what happens to her, C.V. is projecting a futuristic vision of the New Woman in the Indian context. The conventional image of the woman is replaced by an imagined figure that was to emerge on the Indian scene. Another unique feature of this novel is the introduction, for the first time, of untouchables, the channans of south Travancore, Hence is fiction asserting humanistic values over and above the taboos and superstitions of yester-years.